1994
DOI: 10.1046/j.1537-2995.1994.34394196617.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions to group O subjects of 2 units of red cells enzymatically converted from group B to group O

Abstract: These results extend those observed in our earlier 1-unit transfusion studies and suggest that ECO RBCs pose little risk and will be useful in transfusion medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…Isoform III resembled isoform IA in having the same N-terminal amino acid sequence, but it differed from IA and IB in having a more acidic pH optimum, greater thermal stability, greater sensitivity to metal ions and alkylating agents, and anomalous retardation during gel filtration on Sephacryl S-300. Anomalous retardation of ␤-GlcNAc'ase on derivitized dextran gels has also been observed by us 2 and by others (66 -68); it has been ascribed to hydrophobic interactions as well as to charge effects (69).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Isoform III resembled isoform IA in having the same N-terminal amino acid sequence, but it differed from IA and IB in having a more acidic pH optimum, greater thermal stability, greater sensitivity to metal ions and alkylating agents, and anomalous retardation during gel filtration on Sephacryl S-300. Anomalous retardation of ␤-GlcNAc'ase on derivitized dextran gels has also been observed by us 2 and by others (66 -68); it has been ascribed to hydrophobic interactions as well as to charge effects (69).…”
Section: Discussionsupporting
confidence: 66%
“…Lenny and associates (2)(3)(4) have demonstrated that blood group B red cells whose B immunodeterminants were removed by coffee bean ␣-galactosidase survive normally in blood group A and O recipients.…”
mentioning
confidence: 99%
“…Furthermore, there was a commercial application of the enzyme as a supplement in animal feed to increase animal meat production. Finally, rice α-galactosidase may be useful for blood conversion purpose (Harpaz et al 1977;Lenny et al 1994;Zarnitz and Kabat 1960;Zhu et al 1995) since its ability to convert blood type is comparable with that of the taro enzyme (Chien 1991). In fact, we were the first to show that the rice α-galactosidase was capable to convert B red blood cells into O red cells.…”
Section: Discussionmentioning
confidence: 91%
“…Despite this, coffee-bean-derived enzyme was successfully used to complete phase I (Lenny et al, 1991(Lenny et al, , 1994(Lenny et al, , 1995 and phase II clinical trials in which B-ECO RBCs were shown to be safe and functional, providing RBC survival and recovery values equal to ABO-compatible control transfusions in patients during a randomized cross-over study (Kruskall et al, 2000).…”
Section: The Eco Process and The Enzymesmentioning
confidence: 99%
“…Clinical phase I studies were conducted using B-ECO RBCs given to group A and O healthy volunteers and the initial small infusions were escalated to full single RBC units (Lenny et al, 1991), multiple units and finally repeated transfusions (Lenny et al, 1994(Lenny et al, , 1995. A successful phase II cross-over clinical trial in patients was reported in 2000 (Kruskall et al, 2000).…”
Section: Clinical Experience With Eco Rbcsmentioning
confidence: 99%